A New Synthesis - Pierre-Gerlier Forest (Kerman University of Medical Sciences, 2014)
We are on the eve of a revolution in health policy that will forever change our way of thinking about health and healthcare. A few years from now, our vision of the organization and the administration of healthcare services will be transformed. This is not a revolution born out of crisis, albeit the financial pressure on public and private funders of healthcare is clearly at play. It has not been induced by technological change, even if new means of acquiring and analyzing large amount of data-and consequently, unforeseen possibilities of testing hypotheses and answering puzzling questions-are among the most evident determinants of innovation. It is not a revolution driven by a clique or a conspiracy, although I will mention a few (intellectually) leading figures without whom the movement might have been less decisive. It will be the third time in my lifetime that I have witnessed such an upheaval. The first revolution took place in the 1970s, a decade or more before I began my training in health administration. During those years, the field that we now know as "health administration" or "health policy", distinct from medical care or hospital management, emerged as the result of an intellectual breakthrough. It happened when leaders in our discipline realized that instead of just trying to adjust supply to an ever-growing demand, our most important task was to align health services with the population's health "needs".